2002
DOI: 10.1038/labinvest.3780444
|View full text |Cite
|
Sign up to set email alerts
|

MRP6 (ABCC6) Detection in Normal Human Tissues and Tumors

Abstract: M RP6 (ABCC6) is a member of the subfamily of the multidrug resistance proteins (MRPs, reviewed by Borst et al, 2000), but its putative role in multidrug resistance (MDR, reviewed by Moscow et al, 1997) is still under investigation. Closely related proteins such as MDR1 P-glycoprotein (P-gp, ABCB1, reviewed by Ambudkar et al, 1999), breast cancer resistance protein (BCRP, ABCG2;Doyle et al, 1998), and MRP1, -2, and -3 (ABCC1-3) are established MDR transporters. The exact range of substrates for MRP6 has not ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
129
2
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 189 publications
(142 citation statements)
references
References 5 publications
9
129
2
2
Order By: Relevance
“…A similar pattern of transcript expression was reported for the rat MRP6 homologue except that its expression in kidney and gut appeared to be lower and higher, respectively, that the case in humans Madon et al, 2000). In addition, an immunohistochemical analysis in which a monoclonal MRP6 antibody was employed showed that the human protein was abundant in liver and kidney -where it was localized to basolateral surfaces of hepatocytes and proximal tubules, but not expressed in many other tissues including those affected in PXE patients (ie, skin and retina) (Scheffer et al, 2002a). These findings raised the possibility that PXE might result from the absence of a substance that is normally extruded from liver or kidney into blood, and which is involved in connective tissue homeostasis (Uitto et al, 2001).…”
Section: Mrp6mentioning
confidence: 99%
“…A similar pattern of transcript expression was reported for the rat MRP6 homologue except that its expression in kidney and gut appeared to be lower and higher, respectively, that the case in humans Madon et al, 2000). In addition, an immunohistochemical analysis in which a monoclonal MRP6 antibody was employed showed that the human protein was abundant in liver and kidney -where it was localized to basolateral surfaces of hepatocytes and proximal tubules, but not expressed in many other tissues including those affected in PXE patients (ie, skin and retina) (Scheffer et al, 2002a). These findings raised the possibility that PXE might result from the absence of a substance that is normally extruded from liver or kidney into blood, and which is involved in connective tissue homeostasis (Uitto et al, 2001).…”
Section: Mrp6mentioning
confidence: 99%
“…It consists of 31 exons spanning approximately 73kb and encodes for a protein (MRP6, Multidrug Resistance associated Protein 6) belonging to the ATP-binding cassette sub-family C of membrane transporters (Bergen et al, 2000;Le Saux et al, 2000;Ringpfeil et al, 2000). The precise localization in human tissues and the physiological role of MRP6 are still unknown (Scheffer et al, 2002). Recent reports suggest its implication in the cell extrusion of glutathionated metabolites (Belinsky et al, 2002;Ilias et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Based on homology with the well-characterized ABCC1 protein (~45% homology) and its localization on the basolateral membrane of hepatocytes, ABCC6 is thought to be a metabolite pump exporting compounds from these cells [3]. Ilias et al [4] demonstrated in vesicular studies that glutathione S-conjugates, including leukotriene-C4 and N-ethylmaleimide-Sglutathione, are actively transported by the human ABCC6 whereas the endothelin-1 receptor antagonist BQ123 is not efficiently transported in contrast to Abcc6 in rat [5].…”
Section: Introductionmentioning
confidence: 99%